2013
DOI: 10.1002/clc.22158
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of Narrow Fragmented QRS on Admission Electrocardiogram in Patients Hospitalized for Decompensated Systolic Heart Failure

Abstract: Background: Narrow fragmented QRS (fQRS) has recently been recognized as a significant predictor of prognosis in various cardiovascular diseases. Hypothesis: We hypothesized that the presence of narrow fQRS on admission electrocardiogram (ECG) in patients with decompensated systolic heart failure (HF) of any cause would be associated with long-term prognosis. Methods: Patients hospitalized for decompensated HF due to ischemic or nonischemic dilated cardiomyopathy (left ventricular ejection fraction <35%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…As we can see (Table 1), the proportion of patients with fragmentation is reduced from 69% to 64%, but it increases again to 71% at discharge, which may be indicative of the instantaneous local improvement of MI. Based on the results of the study, we noticed that a reduced LVEF below 35% combined with the presence of f-QRS has a value of bad prognosis, which confirmed earlier studies [14]. In the tion of narrow QRS (< 120 ms) is defined as an additional R (R') wave or an incision within the S wave or the presence of at least 2 R-waves in two contiguous leads corresponding to the area by the relevant vasculature coronary artery [9].…”
Section: Resultssupporting
confidence: 89%
“…As we can see (Table 1), the proportion of patients with fragmentation is reduced from 69% to 64%, but it increases again to 71% at discharge, which may be indicative of the instantaneous local improvement of MI. Based on the results of the study, we noticed that a reduced LVEF below 35% combined with the presence of f-QRS has a value of bad prognosis, which confirmed earlier studies [14]. In the tion of narrow QRS (< 120 ms) is defined as an additional R (R') wave or an incision within the S wave or the presence of at least 2 R-waves in two contiguous leads corresponding to the area by the relevant vasculature coronary artery [9].…”
Section: Resultssupporting
confidence: 89%
“…24 In patients with heart failure, as the New York Heart Association (NYHA) class increases, the risk of cardiovascular mortality also increase. 24 In patients with heart failure, as the New York Heart Association (NYHA) class increases, the risk of cardiovascular mortality also increase.…”
Section: Discussionmentioning
confidence: 99%
“…The specific cause of this fractionation on surface ECG and the determinants of this phenomenon are not fully known. Numerous studies have demonstrated that fQRS is associated with increased morbidity and mortality and is also a predictor of adverse cardiac events in patients with ACS [17][18][19], idiopathic dilated [20], and decompensated heart failure [21]. Theoretically, fQRS is generally agreed to be derived from regional myocardial fibrosis/scar and ischaemia, which cause heterogeneous myocardial electrical activation [22][23][24].…”
Section: Discussionmentioning
confidence: 99%